FASCIAL MOBILIZATION TECHNIQUES AS A COMPLEMENTARY STRATEGY IN PHYSIOTHERAPY TO INCREASE MOBILITY AND DECREASE LOW BACK PAIN - Aftemie Alexandra (Sport şi Societate)
The integration of fascial techniques into the kinesiotherapy program for patients with low back pain has demonstrated increased efficacy compared to standard rehabilitation protocols. The aim of the research is to enhance the recovery process for individuals with low back pain by determining the effects of combining specific physiotherapy techniques with fascial mobilizations on mobility improvement and pain reduction. The research hypothesis suggests that evaluating the impact of these combined physiotherapy methods on mobility enhancement and pain alleviation will help identify specific details necessary for developing a model of physiotherapeutic programs. This model will be based on the systematic combination of therapeutic exercises and fascial therapy techniques, which are structured and scientifically validated. Discussion. The most statistically significant differences were recorded in the visual analog scale (VAS) assessments, where the student t-test reached a value of 2.38; P < 0.05, and in the Roland and Morris questionnaire, where the student t-test reached a value of 3.36; P < 0.01 in the control group. Conclusions. Evidence suggests that this combination could be an advanced strategy for the treatment of low back pain, offering benefits that go beyond separate therapies. However, the lack of large and well-controlled studies limits the ability to draw definitive conclusions. By optimizing approaches and improving outcomes for patients with low back pain, a deeper understanding of the integration of physiotherapy and fascial mobilizations will have significant implications for clinical practice.